Directions for the reform process in the Caribbean (ECLAC Port of SpainTT, 1998)
Outlines recent economic performance of the Caribbean countries and some salient issues and problems confronting policy-making. Discusses trading relationships and prospects confronting the Caribbean in the changing regional and world environment. Looks at some of the challenges and issues facing state reform in the Caribbean. Identifies some of the elements and considerations which need to inform the ongoing process of structural reforms.
DC